Performance of ARQ protocols in nonindependent channel errors - Lu, D.-L.; Chang, J.-F. (IEEE transactions on communications, 1993)
The performance of automatic-repeat-request (ARQ) protocols which are affected by nonindependent channel errors is studied. The protocols are the three basic ARQ protocols: stop-and-wait, go-back-N, and selective-repeat. Two types of nonindependent channel errors are considered: the kth-order Markovian errors and the gap errors. Both throughput efficiency and packet delay are obtained. The validity of analysis is verified by computer simulations. One key discovery is that when channel errors are dependent, selective-repeat ARQ achieves the same throughput efficiency as that in independent channel errors.< >